Guyana: from cooperative socialism to economic liberalization and growth : 1976-1994. - GAFAR, John (1996)
Analyses the performance of the economy under statism and economic liberalization, using available macroeconomic indicators. Demonstrates that economic growth resulted from economic liberalization, an 'outward-looking' trade regime, and'market friendly' policies rather than from dirigisme and 'inward-looking' policies.